Seasonal contrasts in individual consistency of oriental honey buzzards' migration. (12th June 2019) - Sugasawa, Shoko; Higuchi, Hiroyoshi
Abstract : Individual consistency in migration can shine light on the mechanisms of migration. Most studies have reported that birds are more consistent in the timing than in the routes or stopover sites during migration, but some specialist species showed the opposite patterns, being more consistent in spatial than temporal aspects of migration. One possible explanation for this contrast is that specialists rely on particular food or habitat resources, which restrict the migratory routes they can take, leading to high spatial consistency. If this is the case, the effect of specialist foraging should become apparent only when birds forage, instead of fasting and flying continuously. To test this effect, we analysed individual consistency in migration of the oriental honey buzzard ( Pernis ptilorhynchus ), a specialist raptor that feeds on honeybees and wasps, using a long-term tracking dataset. As honey buzzards make extended stopovers during which they forage in spring but not in autumn, the spatial consistency should be higher in spring than in autumn. Honey buzzards were highly consistent in both their migratory routes and stopover sites in Southeast Asia, but only during spring migration. Our results highlight an important link between species' migratory consistency and foraging ecology.